HUBUNGAN PEMAHAMAN AKUNTABILITAS, TRANSPARANSI, PARTISIPASI, VALUE FOR MONEY TERHADAP GOOD GOVERNANCE - Eko Suryo Deni Saputro; Mohammad Amin; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThis research was conducted with the aim of: To find out the effect understandingof accountability, transparency, participation, value for money towards goodgovernanceThe population used in this study is the financial staff of Malang OPD whohave received public services. The method used in this research is multiple linearregression method.Based on the results of the research, some conclusions can be drawn,namely: 1) the results of t show that the accountability comprehension variableaffects the good governance, 2) the transparency variable does not have a positiveeffect on good governance, 3) the participation variable has no effect on goodgovernance, 4) the value for money variable does not affect the good governance,F results indicate that the variables of understanding accountability,transparency, participation, value for money affect good governance.Keywords: Accountability, Transparency, Participation, Value for Money andGood Governance.